2020
DOI: 10.1111/hae.13957
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of von Willebrand factor multimers vs activity for von Willebrand disease using modern contemporary methodologies

Abstract: Introduction Diagnosis of von Willebrand disease (VWD) is challenging due to heterogeneity of VWD and test limitations. Many von Willebrand factor (VWF) assays are utilized, including antigen (Ag), activity and multimer analysis. Activity assays include ristocetin cofactor using platelets (VWF:RCo) or other particles incorporating recombinant glycoprotein I (‘VWF:GPIbR’), or other GPI binding assays using gain‐of‐function mutations (‘VWF:GPIbM’), or collagen binding (VWF:CB). Aim To comparatively evaluate mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(55 citation statements)
references
References 33 publications
1
54
0
Order By: Relevance
“…Favaloro et al 20 and Oliver et al 21 have also reported the presence of all HMWM in their type 2M patients, but their studies do not provide any information about its quantification and the diagnosis of type 2M. On the other hand, Bowyer et al 17 and a recent report by Favaloro et al 39 published quantitative HMWM loss in some of the type 2M patients. However, Crist et al 18 and Pikta et al 19 do not mention type 2M VWD in their studies about H5/11VWM.…”
Section: Discussionmentioning
confidence: 96%
“…Favaloro et al 20 and Oliver et al 21 have also reported the presence of all HMWM in their type 2M patients, but their studies do not provide any information about its quantification and the diagnosis of type 2M. On the other hand, Bowyer et al 17 and a recent report by Favaloro et al 39 published quantitative HMWM loss in some of the type 2M patients. However, Crist et al 18 and Pikta et al 19 do not mention type 2M VWD in their studies about H5/11VWM.…”
Section: Discussionmentioning
confidence: 96%
“…22,23 A commercial semiautomated method is now available which offers better standardization and faster turnaroundtime, but which may not be able to evaluate fine details around VWF multimer structures. 24,25 Finally, there are other assays used to further interrogate VWF function, for example (1) the VWF propeptide assay (VWF:pp), which mostly helps to identify VWD types sitting in type 1 with faster VWF clearance, 26 and (2) the VWF-FVIII binding (VWF:FVIIIB). 27 Neither of these assays is widely employed, and instead tends to be only offered by specialist laboratories.…”
Section: Ripa Ristocetin Induced Platelet Aggregation (Agglutination)mentioning
confidence: 99%
“…7,[15][16][17]30 This is "analogous" to adding platelets from a patient with PT-VWD to plasma, and assessing how well plasma VWF binds. There is only one commercial offering for this assay by LIA (Siemens Innovance VWF Ac assay) and this can be performed on Siemens analyzers, 7,16,24,28 and in theory can also be adapted to non-Siemens analyzers. The other main assay type is ELISA, 17,30 but this reflects different methodologies and reagents and is not yet commercially available to this author's knowledge.…”
Section: Vwf:gpibmmentioning
confidence: 99%
See 1 more Smart Citation
“…The main strengths of the new methodology include high reproducibility, ability for same‐day test results, automation of many test steps, and ability to “accurately” identify loss or retention of HMW VWF by both visual and quantitative methods (densitometry). Nevertheless, there are also some limitations, as summarized in another recent publication 18 . One main limitation is the current single agarose gel concentration, limiting identification of VWF structural changes, including an absence of any triplet banding.…”
Section: Vwd Type Classification Description Vwf:ag Vwf:gpib Bindingamentioning
confidence: 99%